FUZZY LOGIC APPLICATION ON EMPLOYEE ACHIEVEMENT ASSESSMENT (CASE STUDY: EDUCATION QUALITY ASSURANCE INSTITUTE OF MALUKU PROVINCE) - Nurhidayah, Nurhidayah; Lesnussa, Yopi Andry; Leleury, Zeth Arthur (PATTIMURA UNIVERSITY, 2022)
Employee achievement assessment in an agency is essential for agency planning and evaluation. Therefore, the Employee achievement assessment must be carried out with a good and appropriate method so that it can guarantee fair and satisfactory treatment for the assessed employees. The value of employee achievement is determined by 60% of the target value of employee achievement and 40% of the average employee behavior value consisting of service orientation, integrity, commitment, discipline, and cooperation. The writing and discussion of this research are about the application of the fuzzy logic Mamdani method using MATLAB software in determining the work performance value of the Maluku Education Quality Assurance Institution (LPMP) employees based on the target value of employee achievement and behavioral values. The Mamdani method’s calculation level of truth is 94%, so it can be concluded that the fuzzy logic of the Mamdani method can be used to measure the performance value of employees.